Intestinal parasitosis and environmental contamination with helminths and protozoa in a Quilombola community of southeast Brazil - Ferreira Pires Eustachio, Priscila; Andrade Avelar, LetÃcia; Leite Dias, JoÃ£o Victor; Mota Queiroz, Dimas Ramon; Gomes Murta, Nadja Maria; Bahia de Oliveira, Gustavo Henrique; Passos Cambraia, Rosana; Rocha Pires, Herton Helder; Rodrigues Martins, Helen (Revista Cubana de Medicina Tropical, 2018)
Introduction: Intestinal parasitosis by helminths and protozoa is still today a global public health problem mainly affecting people living in conditions of social vulnerability, including rural communities. Objective: Describe human intestinal parasitosis and environmental contamination with helminths and protozoa in the Quilombola community of Quartel do Indaiá (of African descent) in the State of Minas Gerais, Brazil. Methods: A cross-sectional study was conducted of stool and soil samples by spontaneous sedimentation, and of plant samples by centrifugation sedimentation, to detect intestinal helminths and protozoa. Water samples were analyzed for total and fecal coliforms. Results: Helminths and protozoa were found in 45.5 % of the people (n = 66). The species detected were Ascaris lumbricoides (18.2 %), Entamoeba coli (18.2 %), Endolimax nana (18.2 %), ancylostoma (6.1 %), Iodamoeba butschlii (4.6 %), Giardia duodenalis (3 %) and Trichuris trichiura (1.5 %). More than one species were present in 19.7 % of the samples. In 18 of the 39 sites sampled, the soil was contaminated with E. coli, E. nana, A. lumbricoides, I. butschlii and/or Enterobius vermicularis. Vegetables (n = 135) were contaminated in 75 samples with 7 of the 8 species analyzed. The contaminants were E. coli cysts, A. lumbricoides eggs and ancylostoma. All water samples were contaminated with total and fecal coliforms. Conclusions: The Quilombola community of Quartel do Indaiá had high levels of human infection and high environmental contamination with intestinal parasites or protozoa, probably due to lack of appropriate sanitary conditions. It is necessary to improve the access to treated water and sanitation.